The integration of crime analysis into police patrol work: Results from a national survey of law enforcement agencies. Issue 3 (12th August 2014) - Boba Santos, Rachel; Taylor, Bruce
Abstract : Purpose: – The purpose of this paper is to examine national survey data of police agencies in the USA to explore the current state of crime analysis integration to patrol crime reduction work. Design/methodology/approach: – The data examined in this paper are from a national quantitative survey which sought to understand how crime analysis results are used by officers as well as higher ranking personnel in the patrol division and what types of strategies are implemented using crime analysis. Findings: – The findings show that the routine use of crime analysis is not well integrated. Despite the low integration, however, some differences were found. Management uses crime analysis the most overall, but officers and first-line supervisors use tactical crime analysis more routinely than management, where management personnel use evaluation most routinely. Tactical crime analysis is used most often for directed patrol, strategic for both directed patrol and general information, and evaluation for both general information and crime prevention. Analysis of using analysis proactively shows that agencies use tactical crime analysis most proactively, followed by the strategic crime analysis, then evaluation. Research limitations/implications: – The study relies on self-report surveys, so the results may suffer from some of the general limitations of self-reports. Also, the study resulted in a lower response rate than surveys of police agencies typically achieve. Although responding and non-responding agencies were comparable in terms of population size, number of officers, and region of the country, the response rate was about 55 percent. However, it is a possibility based on the analysis results that non-responses may reflect a disinterest in the topic or the lack of integration of crime analysis. Originality/value: – This is the first national survey that focussed specifically on crime analysis integration in patrol work for crime reduction. The value of the results presented here are in the description of the current state of crime analysis integration in the USA which has not been investigated in such depth before and the identifications of gaps in both research in practice.